Hegel's Anthropology : Life, Psyche, and Second Nature - De Laurentiis, Allegra (Book collections on Project MUSE., 2021)
"A groundbreaking contribution to scholarship on Hegel and nineteenth-century philosophy, this book makes the case that the "Anthropology" is essential to understanding Hegel's philosophy of spirit in its connection with the philosophy of nature"--